Direct current stimulation induces mGluR5‐dependent neocortical plasticity. Issue 2 (7th July 2016) - Sun, Yan; Lipton, Jonathan O.; Boyle, Lara M.; Madsen, Joseph R.; Goldenberg, Marti C.; Pascual‐Leone, Alvaro; Sahin, Mustafa; Rotenberg, Alexander
Abstract : Objective: To obtain insights into mechanisms mediating changes in cortical excitability induced by cathodal transcranial direct current stimulation (tDCS). Methods: Neocortical slices were exposed to direct current stimulation (DCS) delivered through Ag/AgCl electrodes over a range of current orientations, magnitudes, and durations. DCS‐induced cortical plasticity and its receptor dependency were measured as the change in layer II/III field excitatory postsynaptic potentials by a multielectrode array, both with and without neurotransmitter receptor blockers or allosteric modulators. In vivo, tDCS was delivered to intact mice scalp via surface electrodes. Molecular consequences of DCS in vitro or tDCS in vivo were tested by immunoblot of protein extracted from stimulated slices or the neocortex harvested from stimulated intact mice. Results: Cathodal DCS in vitro induces a long‐term depression (DCS‐LTD) of excitatory synaptic strength in both human and mouse neocortical slices. DCS‐LTD is abolished with an mGluR5 negative allosteric modulator, mechanistic target of rapamycin (mTOR) inhibitor, and inhibitor of protein synthesis. However, DCS‐LTD persists despite either γ‐aminobutyric acid type A receptor or N‐methyl‐D‐aspartate receptor inhibition. An mGluR5‐positive allosteric modulator, in contrast, transformed transient synaptic depression resultant from brief DCS application into durable DCS‐LTD. Interpretation: We identify a novel molecular pathway by which tDCS modulates cortical excitability, and indicate a capacity for synergistic interaction between tDCS and pharmacologic mGluR5 facilitation. The findings support exploration of cathodal tDCS as a treatment of neurologic conditions characterized by aberrant regional cortical excitability referable to mGluR5‐mTOR signaling. Ann Neurol 2016;80:233–246